Benefit of Silver and Gold Nanoparticles in Wound Healing Process after Endometrial Cancer Protocol - Jakub Toczek; Marcin Sadłocha; Katarzyna Major; Rafał Stojko (Biomedicines, 2022)
It is intractable to manage the vast majority of wounds in a classical surgical manner, however if silver, likewise gold and its representative nanoparticles, can lead to the amelioration of the wound healing process after extensive procedures, they should be employed in the current gynecological practice as promptly as possible. Most likely due to its antimicrobial properties, silver is usually applied as an additional component in the wound healing process. In wound management, we obtained various aspects that can lead to impaired wound healing; the crucial aspect for the wound milieu is to prevent the offending agents from occurring. The greatest barrier to healing is represented by the bacterial biofilm, which can occur naturally or in other ways. Biofilm bacteria can produce extracellular polymers, which can then resist concentrated anti-bacterial treatment. The published literature on the use of silver nanoparticles’ utilization in wound healing becomes slightly heterogenous and requires us in difficult moments to set up proper treatment guidelines.